Sistem Manajemen Supervisi Akademik sebagai Kontrol Mutu Kompetensi Pedagogik Guru di Lembaga Pendidikan Madrasah - Hariyanto, Wahid; ‘Indi, Afroyin (Southeast Asian Journal of Islamic Education Management, 2024)
Teachers' problems in carrying out the learning process are very complex. Starting from learning administration skills to teaching skills. This problem must be resolved completely because teachers are the spearhead of quality education whose implications can only be felt in the long term. This study aims to formulate an academic supervision management system as well as the implications arising from the existence of the system in question. This research is qualitative research with a case study type where the process of extracting data is by conducting interviews, observation and documentation. Checking data using extended participation, persistence, and triangulation. Meanwhile, the analysis uses the stages of data collection, data condensation, data presentation, and drawing conclusions. This study resulted in the finding that the academic supervision management system at MTsN 3 Ponorogo is a collaborative-based academic supervision whose supervisor consists of the principal, deputy of principal, and senior teachers with a supervision management cycle consisting of planning, implementation, evaluation and follow-up supervision. The implementation of academic supervision brings changes in understanding for teachers both conceptually and technically, namely knowledge of making learning tools, understanding of student behavior and characteristics, understanding of the use of information technology in the learning process, teacher interest in making changes in attitudes and performance. improve better, and the implementation of learning evaluations is more varied and complex. However, this research needs to be studied from a quantitative perspective to determine how much influence the implementation of academic supervision has on each aspects of teacher pedagogical competence that are not covered in this research.